2010
DOI: 10.1177/1363461510381290
|View full text |Cite
|
Sign up to set email alerts
|

Social Ecology of Child Soldiers: Child, Family, and Community Determinants of Mental Health, Psychosocial Well-being, and Reintegration in Nepal

Abstract: This study employs social ecology to evaluate psychosocial wellbeing in a cross-sectional sample of 142 former child soldiers in Nepal. Outcome measures included the Depression Self Rating Scale (DSRS), Child Posttraumatic Stress Scale (CPSS), and locally developed measures of function impairment and reintegration. At the child level, traumatic exposures, especially torture, predicted poor outcomes, while education improved outcomes. At the family level, conflict-related death of a relative, physical abuse in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
84
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(89 citation statements)
references
References 56 publications
2
84
0
3
Order By: Relevance
“…A representative sample that used multi-level modelling to control for a large number of individual and family variables did not identify a significant association between immigrant concentration and younger children's (5-11 years) internalising problems (Xue et al, 2005). Similarly, applying multivariate regression models to control for village clusters and accounting for a range of individual and family variables, no significant association was identified between high caste proportion and depressive symptoms in adolescent (11-17 years) soldiers of war (Kohrt et al, 2010).…”
Section: Australian and New Zealand Journal Of Psychiatry 49(10)mentioning
confidence: 99%
See 3 more Smart Citations
“…A representative sample that used multi-level modelling to control for a large number of individual and family variables did not identify a significant association between immigrant concentration and younger children's (5-11 years) internalising problems (Xue et al, 2005). Similarly, applying multivariate regression models to control for village clusters and accounting for a range of individual and family variables, no significant association was identified between high caste proportion and depressive symptoms in adolescent (11-17 years) soldiers of war (Kohrt et al, 2010).…”
Section: Australian and New Zealand Journal Of Psychiatry 49(10)mentioning
confidence: 99%
“…Six observational studies (Al-Krenawi and Graham, 2012;Behnke et al, 2010;Kohrt et al, 2010;Simons et al, 2002;Wight et al, 2005;Xue et al, 2005) utilised both selfreport and community measures of minority ethnicity or discrimination. Using the Stouffer method, the combined effect on child depressive symptoms was significant (N = 22,872, p = 0.028, ES = 0.041).…”
Section: Australian and New Zealand Journal Of Psychiatry 49(10)mentioning
confidence: 99%
See 2 more Smart Citations
“…Protective factors in one setting may be risk factors in other settings. For example, political affiliation appeared protective among Nepali former child soldiers (Kohrt et al, 2010), but the reverse was observed in Bosnian adolescents (Jones, 2002). Such complexity warns against pre-packaged resilience promotion approaches in conflict-affected populations, but rather suggests the need for careful assessment of risk -and protective factors in new settings to inform development of mental health prevention and promotion interventions that are tailored to context (Tol et al, 2013).…”
mentioning
confidence: 99%